Assessment of a training program to develop empathy for university students - Falcone, Eliane (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Este estudo avaliou a eficácia de um Programa de This study evaluated the effectiveness of an empathy training (ETP) program in developing empathic behavior among university students. The experimental group consisted of 10 ramdomly designated subjects (three male and seven female) and the control group comprised seven subjects (four male and three female). The subjects were filmed in role play situations, before and after training, with follow up at 30 to 45 days. The verbal and non-verbal content of their behavior of both groups was evaluated by six previously trained, blind adjudicators. The ETP was carried out at I I two-hour encounters. The Student-t and Mann-Whitney tests revealed significant change among the experimental subjects in relation to the control subjects in verbal communication and in four of the 12 aspects of non-verbal communication.